Research on high security G function algorithm - Rui CHEN; Zan LI; Jia SHI; Lei GUAN (物联网学报)
The differential frequency hopping (DFH) overcomes the limitation of frequency hopping and improves the ability to resist tracking interference.The G function determines the DFH sequence and directly affects the performance of DFH communication systems.However,with the complication of wireless communication system such as large capacity DFH network,which poses huge challenges to the use of the number theory based and chaos theory assisted sequence.As a result,in order to improve the security of the system,the novel G function construction was proposed with the aid of hybrid encryption algorithm and the security of hybrid algorithm was analyzed.Moreover,the equivalence principle of G function algorithm and the encryption algorithm was proved.The simulation results show that the DFH sequence generated by the new G function has excellent performance and the performance of the DFH systems is improved greatly.